Lost Tracks: Buffalo National Park, 1909-1939 - Jennifer Brower (Athabasca University Press, 2008)
While contemporaries and historians alike hailed the establishment of Buffalo National Park in Wainwright, Alberta as a wildlife saving effort, the political climate of the early 20th century worked against it. The Canadian Parks Branch was never sufficiently funded to operate BNP effectively or to remedy the crises the animals faced as a result. Cross-breeding experiments with bison and domestic cattle proved unfruitful. Attempts at commercializing the herd had no success. Ultimately, the Department of National Defence repurposed the park for military training and the bison disappeared once more.